ПЕДАГОГІЧНЕ ЗНАЧЕННЯ НАОЧНОСТІ З ПЛАСТИЧНОЇ АНАТОМІЇ НА ЗАНЯТТЯХ ДПМ СПЕЦІАЛЬНОСТІ «ПРАЦЯ» (Педагогіка вищої та середньої школи, 2009)
Principle of construction of by volume evident material on a plartic anatomy on а technological and pedagogical faculty. In this article the problem of study оf plastic anatomy of four-footed animals and birds students is examined through application of by volume eyidcni material on employments after the decoratively-applied art on a technological and pedagogical faculty, It iv shown that a mccextful farmotsbraxuyuschiy process considerably depends on knowledge of plastic anatomy.